PENINGKATAN PRODUKTIVITAS AMPLANG MENGGUNAKAN LEAN SIX SIGMA DI UD KELOMPOK MELATI - Nina Hairiyah; Raden Rizki Amalia; Nuryati Nuryati (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Based on the result of preliminary research at UD Kelompok Melati, in the production process the problem was found, namely the occurrence of waste in the production process. This research purpose to describe the Amplang production process flow, analyze efforts to improve Amplang product productivity with the Lean Six Sigma method and recommend improvements to improve the productivity of Amplang product in UD Kelompok Melati. The production process of Amplang at UD Kelompok Melati begins with sorting of mackerel, cleaning of mackerel, separating meat and bone, milling of mackerel meat, mixing the meatwith mashed seasonings, forming dough, frying, draining and packaging. Efforts to increase productivity at UD Kelompok Melati with the Lean Six Sigma method succeeded in increasing productivity efficiency with a total production time of 113,9 minutes (87,6%) to 94,5 minutes (89,9%) in one production. Recommendations for improving the productivity of Amplang product at UD Kelompok Melati is are proposed layout redesign to reduce waste, create Future Value Stream Mapping (FVSM) and design SOP (Standard Operating Procedure).